Monitoring of economic indicators in the context of financial and economic crises - Dean Sinković; Sebastian Zemla; Nataniel Zemla (Contemporary Economics, 2022)
Financial and economic crises repeat themselves at indefinite intervals. As in the Great Recession (also known as Subprime Crisis) of 2007/2008 there was a bundle of events and processes that preceded it and contributed to its emergence, whether it be economic, political, or ideological. Based on observations presented in this paper, explanations are suggested that crises are significantly related to the development of various indicators. Relevant indicators include the impact of economic indicators (e.g., GDP, key interest rates, debt ratios), capital markets and - as the current Corona Crisis shows - supposedly unforeseen factors or shocks. The study deals with a comparative analysis of indicators regarding both crises and the Great Depression, with the aim of identifying possible trends or patterns. It uses a comparative method and reveals some significant similarities. This insight can be seen as a support for the birth of further crises. The work aims to provide a contribution to current crisis research in a comparative context and to advance findings in the field of early warning and crisis education.
Keywords: E44; E63; H69; N10; N20; 330; Financial and economic crises; economic indicators monitoring and comparison